2016
DOI: 10.3390/ijms17121884
|View full text |Cite
|
Sign up to set email alerts
|

A Jacalin-Related Lectin Regulated the Formation of Aerial Mycelium and Fruiting Body in Flammulina velutipes

Abstract: Flammulina velutipes, one of the most popular mushroom species in the world, has been recognized as a useful model system to study the biochemical and physiological aspects of the formation and elongation of fruit body. However, few reports have been published on the regulation of fruiting body formation in F. velutipes at the molecular level. In this study, a jacalin-related lectin gene from F. velutipes was characterized. The phylogenetic tree revealed that Fv-JRL1 clustered with other basidiomycete jacalin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The significant levels of Fvcpc2 RNAi#43 compared to wild type were calculated by t-test and marked as ** (0.001 < p < 0.01) or *** (p < 0.001). p v−JRL1 = 0.0025, n = 3; p gene9094 = 5.1650E-05, n = 3; p gene10415 = 7.2365E-05, n = 3; p gene10856 = 5.4826E-08, n = 3; p Hyd−1 = 0.0003, n = 3; p Hyd−3 = 0.0001, n = 3; p Hyd−4 = 1.7168E-05, n = 3; p Hyd−6 = 0.0002, n = 3; p FVFD30 = 1.1865E-05, n = 3; p FVFD16 = 0.0009, n = 3; p gene543 = 3.8621E-06, n = 3. basidioma development in F. velutipes (Lu et al, 2016). Our analysis showed that 4 of 9 lectin genes had difference in transcriptional levels between wild type and Fvcpc2 RNAi#43 .…”
Section: Fvcpc2 Positively Regulates Four Lectin Genes In F Velutipesmentioning
confidence: 71%
See 2 more Smart Citations
“…The significant levels of Fvcpc2 RNAi#43 compared to wild type were calculated by t-test and marked as ** (0.001 < p < 0.01) or *** (p < 0.001). p v−JRL1 = 0.0025, n = 3; p gene9094 = 5.1650E-05, n = 3; p gene10415 = 7.2365E-05, n = 3; p gene10856 = 5.4826E-08, n = 3; p Hyd−1 = 0.0003, n = 3; p Hyd−3 = 0.0001, n = 3; p Hyd−4 = 1.7168E-05, n = 3; p Hyd−6 = 0.0002, n = 3; p FVFD30 = 1.1865E-05, n = 3; p FVFD16 = 0.0009, n = 3; p gene543 = 3.8621E-06, n = 3. basidioma development in F. velutipes (Lu et al, 2016). Our analysis showed that 4 of 9 lectin genes had difference in transcriptional levels between wild type and Fvcpc2 RNAi#43 .…”
Section: Fvcpc2 Positively Regulates Four Lectin Genes In F Velutipesmentioning
confidence: 71%
“…In F. velutipes, the lectin encoding gene Fv-JRL1 and its three homolog encoding genes were dramatically upregulated at the primordium formation stage (Liu et al, 2015). F. velutipes Fv-JRL1 positively regulates hyphal growth and fruiting body development (Lu et al, 2016). Thus, enhanced lectin production might be required for normal mushroom formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of expression of jacalin-related lectin-encoding gene Fv-JRL1 was reduced in response to the pdd1 knockdown. According to the results of a previous study (39), Fv-JRL1 positively regulates basidioma development; its transcriptional level was dramatically increased in the primordial stage relative to its expression in the vegetative mycelia, and Fv-JRL1 knockdown severely impaired basidioma development. We found that two genes, gene 10415 and gene 10856, encoding Fv-JRL1 homologs, were also downregulated in the pdd1 knockdown (Data Set S1).…”
Section: Figmentioning
confidence: 75%
“…In F. velutipes, jacalin-related lectin-encoding gene Fv-JRL1 and the two corresponding homolog-encoding genes were upregulated dramatically at the primordium formation stage. Fv-JRL1 promotes hyphal growth and basidioma development (39). Lectin-encoding genes have also been previously shown to be associated with basidioma development in several other fungi (55).…”
Section: Discussionmentioning
confidence: 98%